2016
DOI: 10.1080/00102202.2016.1246440
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Tracers for Combustion Research

Abstract: This review article deals with the use of isotopic tracers in the field of combustion science. A number of researchers have reported the use of isotopic techniques, which have been employed to solve a wide range of combustion problems. Radioactive and stable isotopes have been utilized as tracers, including isotopes of carbon (13 C and 14 C), oxygen (18 O), and deuterium (D). One of the main applications has been to quantitatively determine the propensity of a molecule in a mixture, or specific atom within a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…The degree of contribution of lubricating oil can be quantify by tracing the source of combustion products by using labeling isotope technology Eveleigh et al [54] presented a review on the application of isotope tracers for combustion science and deliberated on the advantages of the various technologies. An initial measuring technique involves adding radioactive Carbon-14 (C 14 ) isotope label into the engine lubricating oil and evaluates the radioactive decay in the BC aerosol compound samples.…”
Section: Effect Of Engine Lubricating Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of contribution of lubricating oil can be quantify by tracing the source of combustion products by using labeling isotope technology Eveleigh et al [54] presented a review on the application of isotope tracers for combustion science and deliberated on the advantages of the various technologies. An initial measuring technique involves adding radioactive Carbon-14 (C 14 ) isotope label into the engine lubricating oil and evaluates the radioactive decay in the BC aerosol compound samples.…”
Section: Effect Of Engine Lubricating Oilmentioning
confidence: 99%
“…The composition of BC aerosol compounds consists mainly of carbon elements, sulfates, nitrates, metals, and traces of other elements [110]. Elemental carbon (EC) and organic carbon (OC) are the main components of carbon in BC aerosol compounds and are associated with the quality of the environment and human health [54]. EC is a component that comes closest to the properties of BC and is produced by the pyrolysis of fuels.…”
Section: Chemical Composition and Element Of Bc Aerosol Compoundsmentioning
confidence: 99%
“…Isotope tracing experiments have indicated that carbons bonded to oxygen atoms are less likely to be involved in soot formation-forming CO and CO2 more readily-while the increase in potential species, such as OH radicals, available due to an increase in oxygen content, has been indicated to limit PAH growth. 67,68…”
Section: Nox Emissionsmentioning
confidence: 99%